2010
DOI: 10.1007/s00595-009-4135-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perioperative peripheral blood values on postoperative complications after esophageal surgery

Abstract: These results suggest that patients who receive preoperative chemoradiotherapy are potentially immunosuppressed, the preoperative serum transferrin level is a possible predictive marker of postoperative pneumonia, and suppression of factor XIII activity is related to anastomotic insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…Anastomotic leakage was observed in five patients (23.8%), a rate somewhat higher than was previously reported (Table 4). Based on our previous reports, high surgical stress is associated with an increased risk of anastomotic leakage 4,32 . The risk of anastomotic leak, however, is impacted by other clinical factors, such as medical comorbidities and preoperative chemoradiotherapy 33 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Anastomotic leakage was observed in five patients (23.8%), a rate somewhat higher than was previously reported (Table 4). Based on our previous reports, high surgical stress is associated with an increased risk of anastomotic leakage 4,32 . The risk of anastomotic leak, however, is impacted by other clinical factors, such as medical comorbidities and preoperative chemoradiotherapy 33 .…”
Section: Discussionmentioning
confidence: 97%
“…Resection and reconstruction of the esophagus is, however, among the most invasive treatments for cancers of the gastrointestinal tract. Although the surgical techniques and perioperative management of esophageal surgery have improved, the morbidity and mortality rates are comparatively high 2–5 …”
Section: Introductionmentioning
confidence: 99%
“…Preoperative CRT is considered to suppress the immune function [21,22]. We previously examined multiple immunological measures in patients with esophageal cancer and found that preoperative treatment induced significant reductions in the total lymphocyte count, phytohemagglutinin response, and natural killer cell activity [23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite ongoing advances in operative techniques and postoperative care, esophageal anastomotic leakage remains a leading cause of morbidity and mortality after esophagectomy [1][2][3]. The major predisposing factors are ischemia of the gastric conduit and errors in surgical technique [4].…”
Section: Introductionmentioning
confidence: 99%